What's trending now? An analysis of trends in internet searches for labor epidurals. (May 2017) - Sutton, C.D.; Carvalho, B.
Highlights: Google searches for labor epidurals are increasing, with 726 000 searches in 2015. Searches for side effects and risks are among the top epidural-related searches. More searches were conducted for 'midwife' or 'doula' than for 'labor epidural'. Abstract: Background: The study aim was to investigate internet use for obtaining information about epidurals for labor and delivery. Methods: Google Trends for US data was queried from 2004 to 2015 to find the most common searches and determine temporal trends. The Google Trends query used the term [epidural] and evaluated changes in search trends over time. Search comparisons were made for each year from 2004 to 2015, and three equal time epochs during the study period (2004–07, 2008–11, 2012–15) were compared. We also compared searches for epidurals with commonly searched birth-related terms. Results: Internet searches are increasing; there were 726 000 searches for [epidural] in 2015. Search terms with the most significant growth in the past 4 years (2012–15) were "birth with epidural, " "pain after epidural, " "labor without epidural, " "epidural birth video, " and "epidural vs natural". Searches for epidural side effects, risks, and pain on insertion were among the most common and were increasing most rapidly. Searches related to epidurals were more common than searches related to "natural births", "home births", and "labor pain", but were less common than searches for "midwives" or "doulas". Conclusion: The findings provide an insight into internet use by those seeking information about labor analgesic options. Identifying the most common and rapidly increasing online search queries may guide physician-parturient interactions and online content creation, to address labor analgesic topics that most interest users.